Reflective Supervision Learning Cycle (RSLC): Integrating Academic Supervision and Internal Quality Assurance to Support SDG 4 Through Sustainable School Improvement - Hilmi Qosim Mubah; Yatim Riyanto; Erny Roesminingsih; Nunuk Hariyati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine how academic supervision is integrated into the Internal Quality Assurance system to support sustainable school improvement and develops a conceptual model that explains the relationship between quality assurance, reflective supervision, professional learning, and continuous improvement. Method: A qualitative case study was conducted at a public Islamic junior secondary school in Pamekasan Regency, Indonesia. Data were collected through semi-structured interviews, observations, and document analysis involving 11 participants selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. Results: Academic supervision was embedded within the Internal Quality Assurance system through five interconnected processes: quality diagnosis, academic supervision planning, reflective supervision, professional learning, and continuous improvement. These processes transformed supervision from a periodic evaluative activity into an evidence-informed organizational mechanism that strengthened instructional quality, professional capacity, and institutional learning. Novelty: The study proposes the Reflective Supervision Learning Cycle (RSLC) as a conceptual and operational framework that integrates academic supervision with Internal Quality Assurance. The model extends existing supervision literature by positioning supervision as the organizational mechanism that connects quality diagnosis, reflective practice, professional learning, and continuous improvement to advance sustainable school improvement and contribute to Sustainable Development Goal 4 (Quality Education).